Terapia fotodinâmica com azul de metileno e etanol: perda óssea alveolar e resposta imune em ratos com periodontite - Campagnolo, Cibele Bruno (2015)
The aim of this study was to evaluate a formulation of methylene blue (MB) with ethanol to antimicrobial photodynamic therapy (aPDT), used as an adjunct to mechanical treatment of experimental periodontitis induced in rats. Forty rats were randomized into five groups: without periodontitis (CN); and periodontitis without treatment (CP); periodontitis underwent three types of treatment: scaling and root planing and irrigation with saline (RAR); scaling and root planing and aPDT with MB diluted in water to 0.01% (aPDT/water); scaling and root planing and aPDT with MB diluted in 20% ethanol (aPDT/ethanol). Periodontitis was induced by placing ligature on the lower right first molar for seven days. Then, the ligatures were removed and the treatments applied. The animals were euthanized seven days after the treatment. The primary outcome was bone loss in the furcation region of the first molar evaluated histometrically. The secondary outcome was the number of osteoclasts immunohistochemically marked for tartrate-resistant acid phosphatase (TRAP). Differences between groups were assessed by One Way ANOVA and post hoc Bonferroni. Thirty-seven rats were subjected to analysis. All three treatment groups showed statistically lower bone loss and smaller number of TRAP positive osteoclasts compared to the untreated group (CP) (P <0.05). No difference was observed for the outcomes between treatment groups (P> 0.05), and between treatments and the negative control (P> 0.05). Bone loss and osteoclastic activity were not changed by aPDT regardless of the inclusion of ethanol in methylene blue formulation when compared to RAR. Therefore, the aPDT did not result in additional benefit when used as adjunctive method to scaling and root planning, considering the parameters evaluated in this study.